Cytochrome P-450 metabolic activity in embryonic and extraembryonic tissue lineages of mouse embryos. - Pedersen, R A (1985)
Mouse morulae, blastocysts, and embryonic and extraembryonic tissue layers were examined for benzo[a]-pyrene metabolism by cytochrome P-450, using the sister chromatid exchange assay. Benzo[a]pyrene exposure in vitro increased sister chromatid exchanges in blastocysts of all genetically responsive mice examined [BALB/cDub, C3H/AnfCum, and outbred Dub:(ICR) strains] but not blastocysts of the nonresponsive AKR/J strain. Benzo[a]pyrene treatment of responsive 7 1/2- and 8 1/2-day (postimplantation-stage) embryos, either intact or as separate tissue layers, increased sister chromatid exchanges in tissues of both embryonic and extraembryonic lineages--i.e., in the embryo proper, in isolated embryonic ectoderm, and in yolk sac, chorion, extraembryonic ectoderm, and extraembryonic endoderm layers. These results indicate that cytochrome P-450 is active in most or all tissues of the early mammalian embryo. It could metabolize xenobiotic molecules reaching the conceptus near the onset of morphogenesis and organogenesis, or it could have another as yet undefined role in normal development.